SOCIALIZATION OF THE USE OF LIQUID ORGANIC FERTILIZER ON CABBAGE PLANTS IN JAGONG JEGET DISTRICT ACEH TENGAH REGENCY: SOSIALISASI PENGGUNAAN PUPUK ORGANIK CAIR PADATANAMAN KUBIS DI KECAMATAN JAGONG JEGET KABUPATEN ACEH TENGAH - Elviani; Nurlia Farida; Tasliati Djafar; Muhammad Iqbal (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
The purpose of this community service activity is to provide farmers with an understanding of the benefits and principles of using liquid organic fertilizer (LOF) to increase cabbage productivity and maintain soil fertility, improve farmers’ skills in making and applying LOF independently by utilizing local organic materials, and encourage the adoption of environmentally friendly technology in cabbage cultivation systems in the highlands of Aceh Tengah. Socialization and Training were carried out in Jagong Jeget District, Aceh Tengah Regency, from July 8 to 10, 2025. The cabbage cultivation land belongs to a local farmer group (selected together with field agricultural extension workers). The results of the Community Service activity include increased farmers’ knowledge, enhanced practical skills in making LOF, adoption of technology, and greater environmental awareness. This socialization activity increased cabbage farmers’ knowledge, skills, and awareness of using liquid organic fertilizer. The participatory and demonstrative methods used in the activity have proven effective in transferring appropriate technology to the farming community.